Effect of continuous lily cropping on rhizosphere microbial structures - Zhang, Yan; Wang, Juan; Zhao, Yan; Liu, Jie (Frontiers in Microbiology, 2025)
Lily is a highly valued economic crop in China, possessing both significant ornamental and medicinal value. However, the phenomenon of farmers repeatedly cultivating lilies in the same area is quite serious, leading to soil nutrient deficiency and a decline in yield and quality. This study focused on the soil of lily continuous cropping as the research object. By analyzing the changes in the physicochemical properties and microbial community structure of lily soil over the same continuous cropping years, the effects of continuous cropping on lily soil were explored. The results show that with the increase of continuous cropping years in lily fields, soil acidification intensifies; the contents of organic matter, nitrogen, phosphorus, and potassium all decrease; the activities of sucrase and acid phosphatase decline; and the activities of catalase, protease, and urease increase. The results revealed the diversity of microbial structures in the rhizosphere soil of the lily “Longya,” providing a theoretical basis for exploring the rules of microbial community change, screening and utilizing beneficial microorganisms, and maintaining the growth and development of lilies.